Ebion at the Barricades: Moral Narrative and Post-Christian Catholic Theology - Barnes, Michel R. (Modern theology, 2010)
My task in this article is to explore the question of the "place" of moral questions—questions of good and evil—in Christian faith, "faith" here being considered particularly as the content or narrative of belief. The thesis I will argue is that Christianity offers no substantial account or explanation of the origin(s) and nature of evil, that in a fundamental way Christianity is not concerned with offering such accounts, and that when the task of supplying accounts of the origin(s) and nature of evil is made central to the content or narrative of Christian faith that faith is made false: it is misunderstood.